Spin state and reactivity of iron(IV)oxido complexes with tetradentate bispidine ligands - Comba, Peter; Faltermeier, Dieter; Krieg, Saskia; Martin, Bodo; Rajaraman, Gopalan (Dalton transactions, 2020)
The iron(IV)oxido complex [(bispidine)FeIVO(Cl)]+ is shown by experiment and high-level DLPNO-CCSD(T) quantum-chemical calculations to be an extremely short-lived and very reactive intermediate-spin (S = 1) species. At temperatures as low as −90 °C, it decays with a half-life of approx. two minutes, and this is the reason why, so far, it remained undetected and why it is extremely difficult to trap and fully characterize this interesting and extremely efficient oxidant. The large difference in reactivity between [(bispidine)FeIVO(Cl)]+ and [(bispidine)FeIVO(MeCN)]2+ (at least two orders of magnitude), while both oxido-iron(IV) complexes have very similar structures and an S = 1 electronic ground state, is presumably due to the large difference in the energy gap between the triplet and quintet electronic states. In presence of cyclohexane as substrate, [(bispidine)FeIVO(Cl)]+ oxidizes cyclohexane with a rate that is approx. 25 times faster than the self-decay of the oxidant, and selectively leads to chlorocyclohexane in moderate yield. The S = 1 electronic ground state of [(bispidine)FeIVO(Cl)]+ and a relatively low gap to the S = 2 state (approx. 6 kJ mol−1vs. approx. 75 kJ mol−1 for [(bispidine)FeIVO(MeCN)]2+) is also predicted by DLPNO-CCSD(T) quantum-chemical calculations. The method used was benchmarked with a set of six ferryl complexes with experimentally known electronic ground states.
Gesehen am 12.05.2020